ICT TO OVERCOME THE STUDENTS’ SPEAKING ANXIETY - Wahyuni, Rina (Premise: Journal of English Education and Applied Linguistics, 2023)
In this digital era, English is the most popular international language. Thus, students have to understand well how to speak in English, but some students feel anxiety when they are asked to speak in English. Thus, in this research, the researcher wants to know whether ICT could minimize the students' anxiety in speaking English. In other words, anxiety is a significant problem for students when the lecturer asks them to speak in front of the class. The sample of this research is 18 students as the total number of students in AKBID Wahana Husada Bandar Jaya in the first semester of the academic year 2022/2023. The research was conducted in AKBID Wahana Husada Bandar Jaya Central Lampung. The researcher used quantitative research, a questionnaire test, and an analysis of the data collected in this research; the researcher used a T-test. The result of this research showed that the use of ICT as media was significantly effective in minimizing the students’ speaking anxiety, and they had a positive perception toward the use of ICT as a media in reducing their anxiety in speaking. The students are more confident in speaking English in front of the class.